Kuzey Kıbrıs Türk Cumhuriyeti kadın giyiminin anadolu kadın giyimi ile bağlantısı - Akdemir, Nihan (My University, 2007)
Tarihsel süreci içerisinde bir çok kültürün yaşadığı Kıbrıs Adası , 1571 yılında Osmanlı İmparatorluğu tarafından fethedilmiştir. Osmanlı İmparatorluğunun fethettiği topraklara Müslüman nüfusu yerleştirme politikası Kıbrıs için de geçerli olmuştur. Bu tarihten itibaren adaya Anadolu’nun bir çok bölgesinden ,büyük çoğunluğu , sürgün yoluyla nüfus aktarımı başlamıştır. Stratejik konumundan dolayı, politik çıkarların en önemli kozu olan Kıbrıs adasında Türkler ve Rumlar, 15 Kasım 1983 tarihinde Kuzey Kıbrıs Türk Cumhuriyeti’nin kurulmasından sonra kesin olarak ayrı yaşamaya başlamışlardır. Kıbrıs Türk toplumunun oluşum yapısı incelendiğinde, Anadolu’nun bazı illerinden göçün yoğun olduğu saptanmıştır. Bu çerçevede Kıbrıs giyiminin bu bölgelerdeki giyimlerle olan benzerlik ve farklılıkları tespit edilmiştir. Rumların giyimiyle benzerlikleri karşılaştırılmıştır. Kıbrıslı Türklerin ve Kıbrıslı Rumların giyim elemanlarının, özel günlerdeki giyim dışında, ortak olduğu fakat detaylarında farklılıkları olduğu görülmüştür. Anadolu’daki kadın giysilerinin, Kıbrıslı Türk kadınları tarafından da kullanıldığı, detaylarında farklılıklar olduğu görülmüştür.

Cyprus, which many cultures lived in her historical process, was conquered in 1571 by Ottoman Empire. The system of Ottoman Empire that placing Muslim people into conquered lands was valid for Cyprus, too. The population dispatches which were mostly in the way of banishment, started from Anatolia to Cyprus after Ottoman conquer. Cypriot Turkish people and Cypriot Greek people definitely started to live in separate sides after 15th of November in 1983 when Turkish Republic of Northern Cyprus was established in island which was the most important trump of political profits because of its strategical location. When the constitution structure of Cypriot Turkish society is examined, we see that the immigration from some Anatolian cites were dominant. In this context, the similarities and the differences of clothing between Cypriot Turkish women and the clothing of women in that cities were determined. Also the similarities and differences of clothing with the Cypriot Greek women were compared. The clothing elements of Cypriot Turkish women and Cypriot Greek women were seen generally similar with differences in details, except clothing during special ceremonies. The clothing elements of Anatolian women were used also by Cypriot Turkish women with some differences in details.
Keywords: Kadın Giyimi_Anadolu_Türkiye; Kadın Giyimi_KKTC (Kuzey Kıbrıs Türk Cumhuriyeti); Testil